Watching Watching: A Review of the New York Times' Digital Platform for TV Viewers. (July 2017) - Patterson, Eleanor
This review critically analyzes the New York Times ' ( NYT 's) digital platform for TV viewing, Watching (https://www.nytimes.com/watching ), and considers how the NYT is trying to use television criticism to produce a commodity audience in the era of peak TV.